Analyzing behavioral pattern in spreading information using social media in Royal Malaysia Police / Rumaizur Rahman Ab. Sattar - Ab. Sattar, Rumaizur Rahman (2017)
Spreading information can be done easily nowadays with the help of new technologies like Internet, hardware and software that support communication. Unfortunately, consciously or not, these new technologies contribute to unethical issues. One of the issues is spreading information. This function can be an issue due to unethical behaviour of the sender or receiver of the information. Royal Malaysia Police (RMP) is a leading enforcement agency in Malaysia. Nowadays, the public confidence in this agency was decreased because of the integrity, attitude, spreading confidentiality information, and other issues. This study will identify the types of behaviour of spreading information in WhatsApp and Facebook among the RMP staff. Aim of this study is to identify the types of behaviour, to identify the relationships between factors of spreading information with intention to spread information and lastly to propose of guidelines about spreading information through WhatsApp and Facebook among the RMP staff. Three objectives were decided for this research. There are to identify the types of behaviour of spreading information in WhatsApp and Facebook among the RMP staff, to identify the relationships between factors of spreading information with intention to spread information among RMP staff, and to propose guidelines on spreading information using WhatsApp and Facebook to be implemented in RMP. The research scope covers on spreading information over the Internet through social media. The social media that will focus on are using WhatsApp and Facebook applications that enable by the users to freely communicate with each other without any boundaries. For this study, the model have created based on Technology Acceptance Model (TAM). It is very popular model, made through adaptation of Theory of Reasoned Action (TRA). TAM is the best model based on the problem area. This study also gives the indirect significant to the public generally which guarantee the well-being of the public in handling the privacy and security of the information indirectly.